Hydrothermal Synthesis, Characterization, and In Vitro Drug Adsorption Studies of Some Nano-BioMOFs. (30th August 2016) - Sattar, Tabinda; Athar, Muhammad; Najamul Haq, Muhammad
Abstract : Three new nano-bioMOFs (NBMOFs) (copper serinate, copper prolinate, and copper threoninate) have been hydrothermally synthesized and characterized by the scanning electron microscopy (SEM). Molecular masses of these nanomaterials have been obtained by mass spectrometric studies. Successful in vitro drug adsorption of rosuvastatin drug has been carried out in these three nanosized materials. The amount of rosuvastatin adsorbed in these materials and its slow release after intervals have been monitored by the high performance liquid chromatography (HPLC). TGA and PXRD spectra of all these materials in pure form and after rosuvastatin adsorption have also been recorded to elaborate the phenomenon of in vitro drug adsorption in these materials.